Is Chronic Urticaria an Autoimmune Disease?: Letter to the Editor - Kandi, Basak; Oguz, Sevilay; Cicek, Demet; Kilic, Nermin; Halisdemir, Nurhan; Saral, Yunus (Ortadogu Ad Pres & Publ Co, 2010)
[Abstract Not Available]
Kronik Ürtiker Otoimmün bir hastalık mıdır
Keywords: Urticaria; autoimmune diseases